1996
DOI: 10.1046/j.1365-2249.1996.d01-757.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of IL-11 and leukaemia inhibitory factor (LIF) do not significantly participate in the production of acute-phase proteins by the liver

Abstract: SUMMARYTo investigate the contribution of IL-11 and LIF to acute-phase protein (APP) production, we first analysed the effects of IL-11 and LIF on production of C-reactive protein (CRP), fibrinogen, and haptoglobin by human primary hepatocytes. We also measured the serum levels of IL-11, LIF, and CRP in serum from patients with inflammatory rheumatic diseases to assess the role of these cytokines in the APP response in vivo. We included patients with conditions associated with a high APP response such as rheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
3
17
1
1
Order By: Relevance
“…However, the transport of such mediators to the liver is most critical in this process. Circulating levels of IL-11 and LIF have previously been reported as being undetectable in RA patients (24,26). We failed to detect serum OSM as well as these 2 cytokines in RA patients, but found that only IL-6 was markedly elevated and correlated with serum CRP levels, which is consistent with previous results (19).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the transport of such mediators to the liver is most critical in this process. Circulating levels of IL-11 and LIF have previously been reported as being undetectable in RA patients (24,26). We failed to detect serum OSM as well as these 2 cytokines in RA patients, but found that only IL-6 was markedly elevated and correlated with serum CRP levels, which is consistent with previous results (19).…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, markedly elevated concentrations of LIF have been detected only in the serum of patients with septic shock and severe tissue damage (24). More importantly, a recent study of human primary hepatocytes has shown that the effects of IL-11 and LIF on hepatocyte APP production were limited compared with the effect of IL-6 (26). Therefore, despite a functional redundancy of IL-6-type cytokines, IL-6 may be a predominant mediator of the acute-phase response when inflammation and tissue damage are localized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of the APP is to control body homeostasis and to regulate the inflammatory reaction. Many neuropoietic cytokines stimulate the release of APP from cultured hepatocytes [8][9][10][11][12], while IL-6 appears to be a primary inducer of APP in vivo [13][14][15]. The acute phase reaction elicited by infection or tissue damage is drastically reduced in IL-6 knockout (KO) mice, while lipopolysaccharide (LPS)-triggered APP secretion is only slightly diminished in these mice [16][17][18].…”
Section: The Acute Phase Reactionmentioning
confidence: 99%
“…6,38 It has also been concluded that circulating levels of IL-11 do not contribute to a major extent to liver acute phase protein production. 39 IL-11 has been found in synovial fluid and in human ovarian follicular fluid. 7 The function of IL-11 in these compartments has been linked to its anti-inflammatory activity and involvement in follicular maturation.…”
Section: Regulation Of Il-11 Secretionmentioning
confidence: 99%